CLINICAL PROFILE OF CHILDREN WITH AND WITHOUT COMORBIDITIES HOSPITALIZED WITH COMMUNITY-ACQUIRED PNEUMONIA - Aurilio, Rafaela Baroni (Rev Paul Pediatr, 2020)
OBJECTIVE: To describe the clinical profile of children and adolescents hospitalized with community-acquired pneumonia (CAP). They were divided into two groups: those with and those without comorbidities. METHODS: An observational, cross-sectional, descriptive study with prospective data collection, was carried out in a cohort of patients aged zero to 11, who were hospitalized with a clinical and radiological diagnosis of community-acquired pneumonia, from January 2010 to January 2012. As an exploratory study, the two groups were compared through logistic regression for possible risk factors associated with community-acquired pneumonia. Relative risk (RR) was used with a 95% confidence interval (95%CI). The process of selection for independent variables was stepwise forward, with a significance level of 5%. RESULTS: There were 121 cases of community-acquired pneumonia evaluated, and 47.9% had comorbidities. In the bivariate analysis, patients with comorbidities demonstrated higher chances for: age >60 months (p=0.005), malnutrition (p=0.002), previous use of antibiotics (p=0.008) and previous hospitalization for community-acquired pneumonia in the last 24 months (p=0.004). In the multivariate analysis, these variables were independent predictors of community-acquired pneumonia in patients with the comorbidities: age >60 months (p=0.002; RR=5.39; 95%CI 1.89-15.40); malnutrition (p=0.008; RR=1.75; 95%CI 1.75-44.60); previous use of antibiotics (p=0.0013; RR=3.03; 95%CI 1.27-7.20); and previous hospitalization for community-acquired pneumonia (p=0.035; RR=2.91; 95%CI 1.08-7.90). CONCLUSIONS: Most patients with community-acquired pneumonia and comorbidities were aged >60 months, were malnourished, had used antibiotics and had been hospitalized for community-acquired pneumonia. Comorbidities were associated with a higher chance of malnutrition and hospitalizations for community-acquired pneumonia in an older age group, compared to children without comorbidities. Knowledge of this clinical profile may contribute to better assist pediatric patients with community-acquired pneumonia hospitalized in referral centers.